Pendekatan Strategi Pemasaran NFT untuk Meningkatkan Kesadaran Konsumen dan Mendorong Tindakan dalam Lingkungan Kripto di Indonesia - Sudirjo, Frans; Enzovani, Senna; Desembrianita, Eva (Universitas Nusa Putra, 2023)
This research investigates the impact of NFT marketing strategies on consumer awareness and action in the Indonesian crypto environment. A mixed methods approach was used, combining quantitative surveys and qualitative interviews. Quantitative results revealed that marketing strategies, including celebrity endorsements and digital art exhibitions, played an important role in raising awareness of NFTs, with approximately 45% of participants citing influential marketing campaigns. Qualitative findings underscored the importance of cultural factors, such as respecting cultural symbols and traditions, in shaping perceptions of NFTs. Challenges include the need for clearer regulations and addressing environmental concerns, while opportunities lie in fostering local NFT communities and supporting emerging artists. This study contributes valuable insights for industry stakeholders looking to navigate the Indonesian NFT landscape.